Criminology: a sociological introduction - Carrabine, Eamonn (Routledge, 2009)
Histories of crime -- Researching crime -- Enlightenment and early traditions -- Early sociologies of crime -- Radicalizing traditions : Marxism, feminism, and Foucault -- Crime, social theory, and social change -- Crime, place, and space -- Victims and victimization -- Crime and property -- Crime, sexuality, and gender -- Crime, emotion, and social psychology -- Organizational and professional forms of crime -- Drugs, alcohol, health and crime -- Thinking about punishment -- The criminal justice process -- Police and policing -- Prisons and imprisonment -- Green criminology -- Crime and media -- Terrorism, state crime, and human rights -- Futures of crime, control, and criminology